T Cell Response in Ischemic Stroke: From Mechanisms to Translational Insights - Zhang, Dianhui; Ren, Jiaxin; Luo, Yun; He, Qianyan; Zhao, Ruoyu; Chang, Junlei; Yang, Yi; Guo, Zhen-Ni (Frontiers in Immunology, 2021)
Ischemic stroke, caused by a sudden disruption of blood flow to the brain, is a leading cause of death and exerts a heavy burden on both patients and public health systems. Currently available treatments for ischemic stroke are very limited and are not feasible in many patients due to strict time windows required for their administration. Thus, novel treatment strategies are keenly required. T cells, which are part of the adaptive immune system, have gained more attention for its effects in ischemic stroke. Both preclinical and clinical studies have revealed the conflicting roles for T cells in post-stroke inflammation and as potential therapeutic targets. This review summarizes the mediators of T cell recruitment, as well as the temporal course of its infiltration through the blood-brain-barrier, choroid plexus, and meningeal pathways. Furthermore, we describe the mechanisms behind the deleterious and beneficial effects of T cells in the brain, in both antigen-dependent and antigen-independent manners, and finally we specifically focus on clinical and preclinical studies that have investigated T cells as potential therapeutic targets for ischemic stroke.